Biomechanics of Mallet Finger - A Case Report - Habib, Md Ahsan; Haque, Molla Ershadul (Journal of Armed Forces Medical College, Bangladesh, 2009)
Aim of the present study is to report a case of mallet finger and exploration of anatomical background of such deformity to have better confidence in management of such cases. doi: 10.3329/jafmc.v5i1.2853 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.49-52